THE POEM AND THE TRANSFORMATION OF THE HORIZON OF EXPECTATION: THE TRAINING OF THE LITERARY READER - Nascimento, Cristiane Aparecida Silva; Lopes, Jair [UNESP]; Manzoni, Rosa Maria Manzoni [UNESP] (FapUNIFESP (SciELO), 2022)
The low reading performance rate identified in external evaluations indicates gaps in the teaching-learning process. This research, at master’s level, aimed to investigate methodologies for the training of literary readers and was carried out in the first grade of a public high school in the state of São Paulo. Through participant research, the teacher-researcher made the decomposition of three skills related to the comprehension of the literary text, that were identified with a higher incidence of errors in the School Performance Evaluation System of the State of São Paulo/2018. and developed a teaching unit consisting of written and artistic productions, video forums, tests and self-assessment, following the receptional method. The results showed the teaching unit helped learning and transformations in the students’ horizon of expectation in relation to the fruition and understanding of literary texts. Thus, the students began to express their critical opinion since they started to develop a more conscious relationship with literature and life.
EL POEMA Y LA TRANSFORMACIÓN DEL HORIZONTE DE EXPECTATIVAS: LA FORMACIÓN DEL LECTOR LITERARIO
O poema e a transformação do horizonte de expectativa: a formação do leitor literário
Keywords: Decomposition of skills; Literary reader; Receptional method